Community health workers in Canada and other high-income countries: A scoping review and research gaps - Najafizada, Said Ahmad Maisam (Can J Public Health, 2015)
OBJECTIVES: Community health workers (CHWs) have been deployed to provide health-related services to their fellow community members and to guide them through often complex health systems. They help address concerns about how marginalized populations in many countries experience health inequities that are due, in part, to lack of appropriate primary health care services, possibly resulting in inappropriate use of higher-cost health services or facilities. This paper reviews studies on CHW interventions in a number of high-income countries, including Canada, to identify research gaps on CHW roles. METHODS: A scoping review using 68 sources of interventions involving CHWs was undertaken. The five-step Arksey and O’Malley model guided this review with the aim of summarizing research findings and identifying research gaps in the existing literature on CHWs in Canada (23 sources). A standardized extraction tool was employed to synthesize the literature. SYNTHESIS: We found that CHWs provide a wide range of health-related services but in a manner that, in Canada, is unrecognized and unregulated. In high-income countries, CHW interventions have contributed to health-related issues in communities and demonstrated potential to both reduce health inequity in marginalized populations and reduce the cost of medical services. CONCLUSION: CHWs are an under-recognized, and therefore underutilized, public health workforce, which has a promising capacity to reduce health inequities in marginalized populations in Canada. There is growing support to suggest that CHW roles need to be better integrated within the broader health and social services systems to enable their full potential to be realized.